RAGAM HIAS SUJI CAIR PADA SULAMAN SELENDANG KOTOGADANG KABUPATEN AGAM SUMATERA BARAT (STUDI KASUS DI YAYASAN AMAI SETIA) - Rahman, Doni; Efi, Agusti; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The research objective was to describe the decorative embroidery on SujiScarves Kotogadang Liquid in terms of design and decorative patterns, andmanufacturing techniques. This type of research is qualitative descriptive. Theinformants are leaders Crafts Amai Setia Foundation, community leaders orbundo kanduang and craftsmen who were 8 people. The technique of collectingdata through interviews, observation and documentation using an interview guideand observation guides. Data analysis technique is data reduction datapresentation and conclusion. The results stated shape design is naturalisticdecoration with floral and leaf. Motifs arranged in a shawl with a size of 2m longand 50cm wide with symmetrical and asymmetrical arrangement. Keharmonisseen from the arrangement and color selection motif. Decorative pattern is a pattern encountered many fill the field. Embroidered making techniques suji cairembroider Kotogadang are: (a) The instrument used was pemedangan, wax paper,carbon paper, needles, and scissors. (b) The material used is a tissue fabric, silk,embroidery threads superior, and thread macau. (c) The process of making themanufacturing phase begins decorative pattern design, installation pemedanganthen proceed with the stitching process by using a variety of skewers.